2020
DOI: 10.15562/gnc.73
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and antioxidant effects of red cabbage on three cancerous cell lines and comparison with a normal cell line (HFF-3)

Abstract: Red cabbage or scientifically Brassica oleracea is a rich source of anthocyanins exhibiting enormous antioxidant properties creating a perspective of its applications in healthcare sector. The aim of this study was the evaluation of antioxidant properties of red cabbage extract by DPPH radical scavenging assay, and exploration of its anticancer activity on the growth and viability of the desired human cancer cells by in vitro assay to detect cytotoxic activity. The results showed enhanced effects with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Purple vegetables, including purple-leaved sweet potato, heartleaf houttuynia, purple-leaved perilla line 1, and bicolored-leaved perilla line 2, can protect lymphocyte DNA against oxidative damage due to their strong antioxidant activities [16]. A study showed that red kale extracts at a concentration of 2500 µg/mL were effective in inhibiting cancer cell growth and increasing the death rate of cancer cells [17]. More than 20 naturally occurring anthocyanins have been identified, and only six are commonly found in higher plants: cyanidin, delphinidin, pelargonidin, peonidin, petunidin, and malvidin [18].…”
Section: Introductionmentioning
confidence: 99%
“…Purple vegetables, including purple-leaved sweet potato, heartleaf houttuynia, purple-leaved perilla line 1, and bicolored-leaved perilla line 2, can protect lymphocyte DNA against oxidative damage due to their strong antioxidant activities [16]. A study showed that red kale extracts at a concentration of 2500 µg/mL were effective in inhibiting cancer cell growth and increasing the death rate of cancer cells [17]. More than 20 naturally occurring anthocyanins have been identified, and only six are commonly found in higher plants: cyanidin, delphinidin, pelargonidin, peonidin, petunidin, and malvidin [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although further investigations are needed, the present study sheds light on the possible anticancer activity of kale and wild cabbage extracts. There are several reports on the cytotoxic effect of cabbages [ 44 , 45 ], broccoli [ 46 , 47 ], and curly kales [ 48 , 49 , 50 ] linked to the richness in polyphenolic compounds and antioxidant activity. There is only rare evidence of anticancer activity of wild Brassica species [ 6 ] and flat-leaved kale [ 36 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prepared concentrations in the study ranged from 625-20000 µg/mL, and the study showed the presence of anti-cancer activity for the studied cancerous cell lines, especially at higher doses. Red cabbage extract also decreased the cell viability of HFF-3 normal cells (IC 50 = 6.4 mg/mL) thus red cabbage extract should not be used at higher concentration than 6.4 mg/mL to avoid normal cell damage (Tajalli et al, 2020).…”
Section: Cytotoxic Activitymentioning
confidence: 99%